Proyecto construcción del centro materno infantil – UNSM Tomo I - Ramírez Reátegui, Augusto (1998)
The health, theme that in San Martin is one of them problems by re so 1 see, especially the reference to the binomial Muki German, which is sees aggravated by several factors between them the growth demographic, the malnutrition, the poverty partner-economic, attention medical poor, infrastructure insufficient, among others; Therefore, the National University of San Martín by the Faculty of Sciences of the Salud-obstetricia, with its human resources and adequate infrastructure, has been required to adhere to all existing health care programs that are committed to overcome the problems of maternal and infant health. The present thesis work provides the spatial solution of the project maternal infant Center - UNSM comprehensively, where the activities inherent to the maternal child care with a capacity for 20 hospital beds and with a covered area of 2,033.46 will be m2. The main objectives of the project are to satisfy the need for care m...